Indicators of Nursing Personnel Supply in Outpatient Medical Care in the Russian Federation during 2010–2018 - V. A. Evdakov; Yu. Yu. Melnikov; A. V. Smyshlyaev (Кубанский научный медицинский вестник, 2020)
Aim. Analysis of the basic indicators of nursing personnel supply of the population and medical organisations providing outpatient care in the public health sector in the Russian Federation over the course of 2010–2018.Materials and methods. The study was conducted using data from the Federal Statistical Observation Form No. 30 “Medical Organization Information” for 2010–2018. Descriptive statistics and comparative analysis were used to assess the country-wide 2010–2018 dynamics of the indicators of nursing personnel supply of the population and medical centres providing outpatient care, including supply with full-time and employed positions, full-time staffing, the ratio of part-time employment, the number and shortage of healthcare workers.Results. For the period 2010–2018, the number of nursing personnel in medical units providing outpatient care increased by 2726 people (an increase of 0.5%), from 542,998 to 545,724. At the same time, the population supply with nursing personnel in outpatient medical units decreased from 38.0 to 37.2 per 10,000 population (a decrease by 2.1%), and staffing of full-time healthcare workers in this category decreased by 6.5%, from 94.2 to 87.7%.Conclusions. The study demonstrates a remarkable shortage of paramedics in outpatient health care (exceeding 200,000 people per annum) over the entire observation period of 2010–2018.